2012
DOI: 10.5604/15093492.1002044
|View full text |Cite
|
Sign up to set email alerts
|

Methods of reducing allogeneic blood demand in orthopedic surgery

Abstract: Despite advances in this field, allogeneic blood transfusion still carries a lot of risk; the availability of heterologous blood is also constantly decreasing. We describe the most popular methods for reducing the allogeneic blood requirement. Basic information is presented about the physiological mechanisms of compensation for intraoperative blood loss, which can be compromised by respiratory and cardiovascular disease or infections. Preoperative anemia (manifested by low hemoglobin levels) is statistically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Preoperative anemia is considered a common factor leading to postoperative blood transfusions, and iron deficiency (ID) is the most common cause of anemia, with a prevalence rate of 41% [6]. Several blood management strategies, such as erythropoietin administration and intravenous (IV) or oral iron supplementation, have been used to achieve optimal preoperative Hb levels and reduce the requirement of postoperative transfusion [7,8]. Studies have indicated that iron supplementation is a safe and efficient method for increasing preoperative Hb levels prior to major orthopedic surgeries [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative anemia is considered a common factor leading to postoperative blood transfusions, and iron deficiency (ID) is the most common cause of anemia, with a prevalence rate of 41% [6]. Several blood management strategies, such as erythropoietin administration and intravenous (IV) or oral iron supplementation, have been used to achieve optimal preoperative Hb levels and reduce the requirement of postoperative transfusion [7,8]. Studies have indicated that iron supplementation is a safe and efficient method for increasing preoperative Hb levels prior to major orthopedic surgeries [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, blood transfusion, in particular the transfusion of red blood cells, is a common practice in orthopedic surgery [2]. In view of potential adverse effects of blood transfusion [3] and an increasing shortage of blood resources, many efforts have been made on the alternatives to transfusion or blood conservation measures to minimize allogeneic blood transfusion, such as acute hypervolemic or normovolemic hemodilution, perioperative blood salvage, use of epoetin alfa to stimulate erythropoiesis, hemostatic agents, deliberate hypotension, and others [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The ideal technique should be easy to perform, have a short onset time, an effect that disappears quickly when drug administration is discontinued, a rapid elimination without toxic metabolites, negligible effects on vital organs, and a predictable and dose-dependent effect. It has been shown that the use of deliberate hypotension can shorten the operative time, reduce the risk of tissue edema caused by ligation or electrocautery, and improve myocardial performance by reducing cardiac preload and afterload [4, 6]. A recent retrospective cohort study indicates that deliberate hypotension has a potential ability to minimize length of hospital stay for patients undergoing orthognathic surgery [7].…”
Section: Introductionmentioning
confidence: 99%